OPTIMALISASI PEMASARAN PRODUK UMKM GERABAH MELIKAN MELALUI PELATIHAN DIGITAL MARKETING - Purwaningtyas Dwi Astuti; Susana Widyastuti; Emi Nursanti; Titik Sudartinah; Erna Andriyanti (Universitas Mataram, 2026)
The development of digital technology requires MSMe players, such as pottery craftsmen, to adapt modern marketing strategies in order to increase competitiveness and market reach. To address this need, the English Literature Study Program Team at UNY carried out a Community Service (PkM) activity to improve digital marketing skills for pottery craftsmen in Melikan Village, Wedi District, Klaten. The activity focused on training in product photography and videography using smartphones, content editing via Canva, utilizing WhatsApp Business, and creating landing pages. The training was conducted using two approaches: (1) experiential learning, where participants were guided to directly apply what they learned, and (2) remote mentoring as a means of consultation and assistance for independent practice. The training outcomes, evaluated through direct observation and questionnaires, showed a significant improvement in participants' understanding and skills in managing digital content as a promotional medium for pottery. Participants found the program highly beneficial, and all expressed a desire for similar follow-up training. This program not only encourages digital independence among artisans in managing product promotions more professionally but also expands the online marketing reach of pottery artisans' products.